1978
DOI: 10.1159/000198115
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Mucins in Health and Disease

Abstract: Intestinal mucins are complex glycoproteins which are secreted from goblet cells, and form a gel-like covering over the mucosal surface. They are assumed to provide lubrication and protection of the underlying epithelium against potentially injurious chemicals, enzymes, bacteria and dietary constituents. Recent advances in our understanding of mucin structure, secretion and functional properties are reviewed in this paper. Implications for diseases such as cystic fibrosis, peptic ulcer, malignancy and inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
117
1
2

Year Published

1981
1981
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(120 citation statements)
references
References 74 publications
0
117
1
2
Order By: Relevance
“…The high viscosity and acidity of acid mucus enables resistance against the attack of bacterial enzymes (Fontaine et al, 1996 andDeplancke andGaskins, 2001). This is important in the caecum as it is regarded as a site for bacterial fermentation in herbivores (Forstner, 1978).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high viscosity and acidity of acid mucus enables resistance against the attack of bacterial enzymes (Fontaine et al, 1996 andDeplancke andGaskins, 2001). This is important in the caecum as it is regarded as a site for bacterial fermentation in herbivores (Forstner, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Although the present study did not determine the thickness of the mucous layer a significant increase in the total number of goblet cells per total area was observed in all three species for both staining methods. Similarly, an increase in numbers of mucus secreting goblet cells is present in the colon of the human (Forstner, 1978) and three insectivorous mammalian species (Boonzaier et al, 2013). Due to the vulnerability of sialomucins to bacterial degradation, sulfomucin secreting cells are expected to dominate in the large intestine where the bacterial load is high (Fontaine et al, 1996, Deplancke and Gaskins, 2001, Hino et al, 2012and Machado-Neto et al, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, GPs layer of gastrointestinal tract protects the epithelial cells and mucosa from proteolytic enzymes invasion of enteric bacteria, bacterial and environmental toxins, and some dietary components [21,22] . This glycoprotein compounds also known as mucins which secreted by goblet cells [23] . Various authors have suggested that goblet cells contain neutral or acidic mucin glycoproteins or the combination of both types of mucin [24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…Mucins are expressed by various epithelial cell types that exist in relatively harsh environments [2] . Mucins' key characteristic is its ability to form gels; therefore they are a key component in most gellike secretions, serving functions such as lubrication, cell signaling and forming chemical barriers [3].…”
Section: Introductionmentioning
confidence: 99%